A Numerical Investigation on Microphysical Properties of Clouds and Precipitation over the Tibetan Plateau in Summer 2014 - Tang, Jie; Guo, Xueliang; Chang, Yi (Journal of Meteorological Research, 2019)
In order to improve our understanding of microphysical properties of clouds and precipitation over the Tibetan Plateau (TP), six cloud and precipitation processes with different intensities during the Third Tibetan Plateau Atmospheric Science Experiment (TIPEX-III) from 3 July to 25 July 2014 in Naqu region of the TP are investigated by using the high-resolution mesoscale Weather Research and Forecasting (WRF) model. The results show unique properties of summertime clouds and precipitation processes over the TP. The initiation process of clouds is closely associated with strong solar radiative heating in the daytime, and summertime clouds and precipitation show an obvious diurnal variation. Generally, convective clouds would transform into stratiform clouds with an obvious bright band and often produce strong rainfall in midnight. The maximum cloud top can reach more than 15 km above sea level and the velocity of updraft ranges from 10 to 40 m s −1 . The simulations show high amount of supercooled water content primarily located between 0 and −20°C layer in all the six cases. Ice crystals mainly form above the level of −20°C and even appear above the level of −40°C within strong convective clouds. Rainwater mostly appears below the melting layer, indicating that its formation mainly depends on the melting process of precipitable ice particles. Snow and graupel particles have the characteristics of high content and deep vertical distribution, showing that the ice phase process is very active in the development of clouds and precipitation. The conversion and formation of hydrometeors and precipitation over the plateau exhibit obvious characteristics. Surface precipitation is mainly formed by the melting of graupel particles. Although the warm cloud microphysical process has less direct contribution to the formation of surface precipitation, it is important for the formation of supercooled raindrops, which are essential for the formation of graupel embryos through heterogeneous freezing process. The growth of graupel particles mainly relies on the riming process with supercooled cloud water and aggregation of snow particles.